Striking the Right Balance Determines TB or Not TB - BoseDasgupta, Somdeb; Pieters, Jean (Frontiers in Immunology, 2014)
Mycobacterium tuberculosis continues to be one of the most successful pathogens on earth. Upon inhalation of Mycobacterium tuberculosis by a healthy individual, the host immune system will attempt to eliminate these pathogens using a combination of immune defense strategies. These include the recruitment of macrophages and other phagocytes to the site of infection, production of cytokines that enhance the microbicidal capacity of the macrophages as well as the activation of distinct subsets of leukocytes that work in concert to fight the infection. However, being as successful as it is, M. tuberculosis has evolved numerous strategies to subvert host immunity at virtual every level. As a consequence, one third of the world inhabitants carry M. tuberculosis, and tuberculosis continuous to cause disease in more than 8 million people with deadly consequences in well over 1 million patients each year. In this review, we discuss several of the strategies that M. tuberculosis employs to circumvent host immunity, as well as describe some of the mechanisms that the host uses to counter such subversive strategies. As for many other infectious diseases, the ultimate outcome is usually defined by the relative strength of the virulence strategies employed by the tubercle bacillus versus the arsenal of immune defense mechanisms of the infected host.